VD_FINDINFO HC / 2014 / 879 vom 20. August 2014 - VD Tribunal cantonal (2014)
CONTRAT D'ENTREPRISE, ESCOMPTEPRIX, PRIX, FORFAIT, MESURAGE, NORME SIA, INTÉRÊT MORATOIRE, DEMEURE | 18 CO, 363 CO, 373 CO, 374 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)